Disorders of Sex Development: Can You Be Sure This Baby Is A Boy or Girl? We Must See Beyond The Diagnosis (Journal of Shaheed Suhrawardy Medical College, 2019)
Throughout the pregnancy, the parents have anticipated whether their child will be a boy or a girl. No part of a newborn baby’s anatomy arouses as much interest initially as the external genitalia. Most newborn children have the typical features of a boy or girl, but in some cases the baby’s sex can’t be clearly identified. Infants born with ambiguous or abnormal genitalia may have indeterminate phenotypic sex.1 Disorders of sex development (DSDs), formerly termed intersex conditions, are congenital conditions in which development of the chromosomal, gonadal, or anatomic sex is atypical and may affect up to 1:1000 individuals in the population.2J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 103-110